Clinical utility of secukinumab in moderate-to-severe scalp psoriasis: evidence to date - Kivelevitch D; Amin S; Menter A (Dove Medical Press, 2019)
Dario Kivelevitch,1 Sima Amin,2 Alan Menter11Baylor University Medical Center, Dallas, TX, USA; 2Texas A&M College of Medicine, Bryan, TX, USAAbstract: Psoriasis is an immune-mediated inflammatory dermatosis commonly affecting the scalp and fringes of the face, neck and ears. It may be difficult to treat and the presence of extensive and highly visible lesions may significantly influence psychosocial well-being. Secukinumab, a monoclonal antibody that selectively targets interleukin-17A and has been shown to provide robust and sustained efficacy for whole body psoriasis. In this review, we evaluate the evidence to date of secukinumab in patients with moderate-to-severe scalp psoriasis. A comprehensive Cochrane database and PubMed searches of all available literature in English through September 2018 was performed using the search terms: “psoriasis”, “scalp” and “secukinumab”. Based on current evidence, we conclude that secukinumab is efficacious and well-tolerated treatment for patients with moderate-to-severe scalp psoriasis. Further studies are however warranted.Keywords: secukinumab, psoriasis, scalp, therapy